Exergy analysis of heat assisted ejector refrigeration system using R1234yf. Issue 1 (March 2021) - Sharma, Bharat; Sachdeva, Gulshan; Kumar, Vikas
Abstract: An ejector refrigeration system (ERS) is introduced which operates on low-grade energy like solar energy, industrial waste heat etc. In this paper, the performance parameters and the conventional exergy analysis of ejector refrigeration system is measure with reference to ambient conditions. Exergy analysis was applied independently to each component of the system. The refrigerant R1234yf which has low Ozone depletion potential (ODP) and Global depletion potential (GWP) has been used to analysed the exergy analysis with the help of Engineering Equation solver software. The results shows that maximum exergy destruction in generator followed by ejector and other components.